2019
DOI: 10.3390/agronomy9080442
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Alien Invasive Weeds under Climate Change Scenarios in Mountainous Bhutan

Abstract: Climate change is viewed as a cause in accelerating the rate of invasion by alien species in addition to the globalization of anthropogenic activities. Ecological niche modeling has become an instrument in predicting invasion from natural or invaded ranges to uninvaded ranges based on the presence records of organisms and environmental parameters. This study explored the changes in the distributions of globally noxious alien species (Aegratina adenophora, Ageratum conyzoides, Chromolaena odorata, Lantana camar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
0
15
1
Order By: Relevance
“…Yet, species distribution modelling has never been used, especially in spatial planning and decision-making in the context of plant invasion. Thinley et al (2019) tried to model six alien invasive species, including parthenium weed in Bhutan using the most commonly implemented MaxEnt tool (Santini et al 2021). However, the study did not provide appropriate details in terms of districts suitability and elevational changes other than range expansion, contraction, and directional change, which have limited use when planning for management programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, species distribution modelling has never been used, especially in spatial planning and decision-making in the context of plant invasion. Thinley et al (2019) tried to model six alien invasive species, including parthenium weed in Bhutan using the most commonly implemented MaxEnt tool (Santini et al 2021). However, the study did not provide appropriate details in terms of districts suitability and elevational changes other than range expansion, contraction, and directional change, which have limited use when planning for management programs.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the study conducted by Thinley et al (2019) and Chhogyel et al (2021), no study had been conducted on IAPS distribution in Bhutan. Both the studies implemented the most commonly used species distribution modelling program (-MaxEnt ) (Santini et al 2021) and provided a general overview of parthenium weed distribution at the national level and West-Central region, respectively under current and a future climate (predicted for 2070).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies in other parts of the world have also predicted the expansion of climatically suitable areas for A. adenophora in future climate scenarios (Wang and Wang 2006;Zhu et al 2007;Wang et al 2017;Lamsal et al 2018;Thapa et al 2018). However, a study conducted in Bhutan predicted a contraction of suitable areas for A. adenophora by 0.22% in 2050 (Thiney et al 2019). An experimental warming study conducted in China revealed that warming (28C rise) increased biomass allocation and canopy cover of the weed, making it more stress tolerant (He et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change has a profound effect on the introduction and establishment of invasive species (Roura-Pascual et al 2011). Climate warming could facilitate the dispersal and performance of invasive alien species, which would allow range expansion and new invasions (Thiney et al 2019;Walther et al 2009). Moreover, climate change facilitates the distribution of alien species into new areas through removing constraints to species dispersal and survival such as temperature or moisture (Hellmann et al 2008;Mainka and Howard 2010).…”
Section: Introductionmentioning
confidence: 99%